Overseas Hospitality Students Internship Program Experiences - Rina Kurniawati; Mahalita Tri Nikita Bangun; Heru Suheryadi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this paper to gather insights on students’ experiences during their overseas internship program. This paper discusses the difficulties faced by the students during their overseas internship program and their approaches to overcome them. Insights might be useful as feedback and lesson learned for education institutions. This paper employs a qualitative approach. The data collected were secondary data. 12 (twelve) students’ internship reports were gathered with purposive sampling method. A thematic data analysis was employed. The results suggest that difficulties encountered by the students in three areas: cultural difference, language and communication, and task management. This paper offers insights on the students’ approach to overcome the difficulties. Educational institutions need to better understand the needs and expectations of the parties involved, to better prepare the students, and monitor the program from the beginning until its completion.